Nanozyme-Triggered Cascade Reactions from Cup-Shaped Nanomotors Promote Active Cellular Targeting - Xin Wang; Zhongju Ye; Shen Lin; Lin Wei; Lehui Xiao (Research, 2022)
Self-propelled nanomotors have shown enormous potential in biomedical applications. Herein, we report on a nanozyme-powered cup-shaped nanomotor for active cellular targeting and synergistic photodynamic/thermal therapy under near-infrared (NIR) laser irradiation. The nanomotor is constructed by the asymmetric decoration of platinum nanoparticles (PtNPs) at the bottom of gold nanocups (GNCs). PtNPs with robust peroxidase- (POD-) like activity are employed not only as propelling elements for nanomotors but also as continuous O2 generators to promote photodynamic therapy via catalyzing endogenous H2O2 decomposition. Owing to the Janus structure, asymmetric propulsion force is generated to trigger the short-ranged directional diffusion, facilitating broader diffusion areas and more efficient cellular searching and uptake. This cascade strategy combines key capabilities, i.e., endogenous substrate-based self-propulsion, active cellular targeting, and enhanced dual-modal therapy, in one multifunctional nanomotor, which is crucial in advancing self-propelled nanomotors towards eventual therapeutic agents.